SPECT Imaging of Acute Disc Herniation by Targeting Integrin α5β1 in Rat Models - Guan, Jian; Yuan, Chenghua; Tian, Xin; Cheng, Lei; Gao, Hannan; Yao, Qingyu; Wang, Xinyu; Wu, Hao; Chen, Zan; Jian, Fengzeng (Frontiers in Neurology, 2022)
Objective Traditional morphological imaging of intervertebral disc herniation (IVDH) is challenging in early disease diagnosis. Aiming to early diagnosis of IVD by non-invasive molecular imaging targeting Integrin α5β1, we performed a novel imaging in the rats with acute IVDH for the first time. Methods Animal models were prepared by conducting an established needle puncture procedure through the normal IVD. The disc-injured rats were performed SPECT/CT imaging of 99mTc-3PisoDGR2 peptide at 1 day~2 months post-injury. The expression change of integrin α5β1 was determined by anti-integrin α5 and anti-integrin α5 β1 immunohistochemistry. The MRI was performed for a comparation during the disease progression. The morphological changes of the disc were determined by Safranin-O staining. Results The rats with acute IVDH show gradually increased disc uptake of 99mTc-3PisoDGR2 from 1~7 days post-treatment, and descending with a significantly high level than that of the normal discs in the degenerative diseases. Immunohistochemistry results show the expression of Integrin α5β1 on the surface of annulus fibrosus (AF) cells and nucleus pulposus (NP) cells and the results were in agreement with a similar trend. MRI showed a progressively decreased T2 density and MRI index throughout the investigation. HE and Safranin-O staining exhibited a disorganized structure of IVD as well as the loss of proteoglycan after the puncture. Conclusions: Our proof-of-concept study demonstrated a well correlation of Integrin α5β1 expression and acute disc herniation. The SPECT/CT imaging of 99mTc-3PisoDGR2 targeting Integrin α5β1 could diagnosis IVDH in an acute phase for early disease management.